Assessing Health Outcomes After Environmental Exposures Associated With Open Pit Burning in Deployed US Service Members. (August 2016) - Rohrbeck, Patricia; Hu, Zheng; Mallon, COL Timothy M.
Abstract : Objective: This study assessed the long-term health impact of environmental exposures associated with open pit burning in deployed US service members. Methods: Two hundred individuals deployed to Balad, Iraq, and Bagram, Afghanistan, with known exposure to open pits, were matched to 200 non-deployed service members. Both cohorts were observed for adverse health outcomes after returning from deployment. Results: Slight increased risks were observed for respiratory diseases in the Bagram cohort (adj RR: 1.259), and for cardiovascular disease in the Balad cohort (adj RR: 1.072), but the findings were not significant. The combined deployed cohort showed lower risks for adverse health outcomes, suggesting a healthy deployer effect. Conclusions: In conclusion, this study did not find significantly increased risks for selected health outcomes after burn pit exposure during deployment among two deployed cohorts compared with a non-deployed cohort.